Bis{μ-2-(1H-indol-3-yl)-N'-[1-(5-methyl-2-oxidophen-yl)ethyl-idene]-aceto-hydraz-idato}bis-[aqua-zinc(II)] dimethyl sulfoxide tetra-solvate - Zuraini, Kadir; Ali, Hapipah Mohd; Puvaneswary, Subramaniam; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The dinuclear title compound, [Zn(2)(C(19)H(17)N(3)O(2))(2)(H(2)O)(2)]·4C(2)H(6)OS, lies about a center of inversion. The deprotonated monoanion O,N,O-chelates the Zn atom; the hydr-oxy O atom also engages in bonding to the symmetry-related Zn atom so that one N and three O atoms form a square around the metal. The coordination geometry is square-pyramidal, with the apical site occupied by a water mol-ecule. Hydrogen bonds, with the water mol-ecule serving as donor atom, lead to the formation of a linear chain motif. There is an N-H⋯O hydrogen bond between the complex molecule and solvent O atom.